(untitled) (Research, Society and Development, 2024)
The discussion surrounding the use and abuse of psychoactive substances is becoming increasingly prominent in the academic environment. Within this complex theme, an emerging approach that is gaining prominence is that of harm reduction, which presents itself as an alternative to traditional mandatory abstinence. This narrative review aims to explore the knowledge and practices of users, family members and harm reduction agents about harm reduction based on the literature. The index terms “harm reduction” and “drugs” were used, and after applying the selection criteria, 6 articles were identified that emphatically explore the perspective of users, family members and harm reducers about harm reduction. The main topics were: autonomy, social reintegration, practices in harm reduction and the lack of knowledge of the subject by these actors. Thus, it is necessary to bring these subjects closer to the process of implementing harm reduction practices in dealing with problems related to the use of psychoactive substances.